Unbiased solar energy storage: Photoelectrochemical redox flow battery - João Azevedo (2016)
Electricity from renewable energy sources is craving for efficient storage technologies, in particular solar industry, to enable practical small-scale solutions for residential and offices use. The best stationary technology is probably the redox flow batteries. This article proposes the direct conversion of sunlight into electrochemical energy stored in a redox flow battery. A photoelectrochemical cell is used to charge a vanadium redox flow cell (CdS(s)|V3+, VO2+||V3+, V2+|Carbon Felt(s), E0 =0.6 VNHE). A CdS thin film photoelectrode is prepared to directly charge the cell, pairs V3+/VO2+. CdS photoanode exhibits competitive photocurrents, when compared to other photoelectrochemical devices, and yields enough photovoltage to charge the vanadium battery up to 75% with no external bias. An overlayer of CdSe improves the performance of CdS with current densities up to ca. 1.4 mA cm2 . Finally, a tandem configuration is tested using a dye-sensitized solar cell and a CdS photoanoade creating 1.3 V of photovoltage. This tandem arrangement proves to charge conventional all vanadium redox cell (DSC/CdS(s)|VO2+, VO2 +||V3+, V2+|Carbon Felt(s), E0 =1.2 VNHE) without external bias.